Diseminasi Teknologi Retort Drum untuk Produksi Biochar Bambu Di Desa Banjar Waru, Cilacap - Sari Widya Utami; Galih Mustiko Aji; Artdhita Fajar Pratiwi; Fadillah Fadillah; Rostika Listyaningrum (LPPM IT Telkom Purwokerto, 2024)
The purpose of this community service activity is to enhance community knowledge and skills in making bamboo craft waste into biochar using retort drum technology. Bamboo biochar produced by using retort drum technology will be used to enhance the relatively low fertility of agricultural soil in Banjar Waru village. The way for carrying out community service activities involves introducing biochar and its manufacturing procedures, training in biochar production, and evaluating the longing program. The activity's results showed that participants were interested in and noticed the process of making bamboo waste into biochar. The effectiveness of this community service activity is that there is a program conducted in groups to produce bamboo charcoal and other agricultural waste.